Requirements for dynamical differential phase contrast x-ray imaging with a laboratory source. (28th November 2016) - Macindoe, David; Kitchen, Marcus J; Irvine, Sarah C; Fouras, Andreas; Morgan, Kaye S
Abstract: X-ray phase contrast enables weakly-attenuating structures to be imaged, with bright synchrotron sources adding the ability to capture time sequences and analyse sample dynamics. Here, we describe the translation of dynamical differential phase contrast imaging from the synchrotron to a compact x-ray source, in order to achieve this kind of time sequence imaging in the laboratory. We formulate broadly-applicable set-up guidelines for the single-grid, single-exposure imaging technique using a divergent source, exploring the experimental factors that restrict set-up size, imaging sensitivity and sample size. Experimental images are presented using the single-grid phase contrast technique with a steel attenuation grid and a liquid-metal-jet x-ray source, enabling exposure times as short as 0.5 s for dynamic imaging. Differential phase contrast images were retrieved from phantoms, incorporating noise filtering to improve the low-count images encountered when imaging dynamics using short exposures.